Transformation of the Classical genre: Quadratus and beginnings of Christian apology - Ališauskas, Vytautas (Literatūra, 2019)
Quadratus belonged to the second generation of Jesus’ followers. At the early stage of his life he was an itinerant preacher of the Gospel, also visiting Asia Minor in the course of his travels. It was there that he may have received information about the persons who had directly experienced Jesus’ beneficence. After he settled in Athens, Quadratus, just like other Athenian apologists, Aristides and, later, Athenagoras, was not part of the Church hierarchy, but, more likely, a free teacher. When Hadrian was visiting Athens, he was presented with an apology which should have provided the emperor with reliable information concerning the new religion. The paper suggests a hypothesis that the direct impulse to defend Christianity was the conflict between the Christians and the Athenian society on the issue of the Eleusinian mysteries. Quadratus’ apologetic opus, among other topics of which we have no knowledge, discussed the unique character of the miracles performed by Christ, comparing them to the deeds of the demigods or of the contemporary miracle-workers. It also (according Martyrologium of Bede the Venerable) discussed the nature of Christian food, emphasising its ordinary character. Just as the Letter to Diognetus, it probably suggested that the Christian way of life and customs were not different from those of other people.